2012
DOI: 10.1021/cn3000907
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterases as Therapeutic Targets for Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia among the elderly. In AD patients, memory loss is accompanied by the formation of beta-amyloid plaques and the appearance of tau in a pathological form. Given the lack of effective treatments for AD, the development of new management strategies for these patients is critical. The continued failure to find effective therapies using molecules aimed at addressing the anti-beta amyloid pathology has led researchers to focus on other non-amyloid-based app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 148 publications
(352 reference statements)
3
179
0
1
Order By: Relevance
“…Puzzo et al [130] first demonstrated the preclinical efficacy of PDE5 inhibitors in AD mouse models and the findings were later confirmed by other groups [131][132][133]. Among reported PDE5 inhibitors, tadalafil and sildenafil can penetrate into the brain and ameliorate synaptic, learning, and memory deficits by modulating the cyclic guanosine monophosphate intracellular signaling pathway [130,134].…”
Section: Phosphodiesterase 5 Inhibitorsmentioning
confidence: 90%
“…Puzzo et al [130] first demonstrated the preclinical efficacy of PDE5 inhibitors in AD mouse models and the findings were later confirmed by other groups [131][132][133]. Among reported PDE5 inhibitors, tadalafil and sildenafil can penetrate into the brain and ameliorate synaptic, learning, and memory deficits by modulating the cyclic guanosine monophosphate intracellular signaling pathway [130,134].…”
Section: Phosphodiesterase 5 Inhibitorsmentioning
confidence: 90%
“…Since cAMP response element-binding (CREB) may be modulator of processes required for memory formation (96). Rolipram was the first compound found to effectively restore cognitive defect in Alzheimer's disease animal models (97). Furthermore, roflumilast and rolipram ameliorate hypertension-induced impairment of learning and memory functions in rats (98).…”
Section: Future Direction Of Pde4 Inhibitorsmentioning
confidence: 99%
“…predicted to have anti-inflammatory effects [6]. Due to their presence in immune cells, the PDE4 family of enzymes represents a potential therapeutic target to induce immune suppression [105][106][107][108]. Thus, the PDE4 family of enzymes represents a promising target in the treatment of cutaneous inflammatory conditions [109].…”
Section: Type 4 Phosphodiesterases and Their Role In Chronic Inflammamentioning
confidence: 99%